Correction: Bright middle cerebellar peduncle sign in multiple system atrophy with predominant cerebellar ataxia is more apparent in double-inversion recovery imaging than in conventional imaging. - Wataru Shiraishi; Ayano Matsuyoshi; Yusuke Nakazawa; Yukiko Inamori; Akira Yogi; Tetsuya Hashimoto (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0313651.].